Digital Food Environments and Hidden Obesity Risk Among Urban Youth: a Mixed-Methods Study - Isah Fitriani; Abdul Rahman La Ede; Azizatul Hamidiyah (PT. Anagata Sembagi Education, 2026)
The development of digital technology has transformed the urban food environment through the increased use of food delivery apps and exposure to digital food promotions, potentially posing latent health risks to young people. This study aimed to analyze the relationship between the digital food environment and the risk of latent obesity among urban youth using a mixed methods approach. A sequential explanatory design was implemented with a quantitative phase involving 240 young people aged 18–30 years, followed by a qualitative phase through in-depth interviews with high-risk participants. Quantitative data were collected through body composition measurements and a digital food environment exposure questionnaire, then analyzed using multivariate statistics. The results showed that 34.6% of respondents with a normal body mass index (BMI) experienced latent obesity, and exposure to a high digital food environment significantly increased the risk of latent obesity. Qualitative findings revealed the normalization of high-calorie food consumption in digital spaces, efficiency-based rationalizations, and low awareness of latent obesity. The integration of findings indicates that the digital food environment not only influences consumption patterns but also shapes youth's perceptions and behavioral justifications. This study confirms that the digital food environment is a structural determinant of latent obesity risk, necessitating prevention strategies that include digital health literacy, regulation of online food promotions, and the use of more comprehensive health indicators.